C-reactive protein/albumin ratio is the most significant inflammatory marker in unresectable pancreatic cancer treated with FOLFIRINOX or gemcitabine plus nab-paclitaxel - Tsuyoshi Shirakawa; Akitaka Makiyama; Mototsugu Shimokawa; Taiga Otsuka; Yudai Shinohara; Futa Koga; Yujiro Ueda; Junichi Nakazawa; Satoshi Otsu; Azusa Komori; Shiho Arima; Masaru Fukahori; et al. (Scientific Reports, 2023)
Abstract There are limited absolute biomarkers for determining the prognosis before first- and second-line palliative chemotherapy in unresectable pancreatic cancer (urPC) patients. To find the best prognostic inflammatory marker, we investigated relationships between overall survival (OS) and six inflammatory markers; C-reactive protein/albumin ratio (CAR), neutrophil–lymphocyte ratio (NLR), prognostic nutrition index (PNI), platelet–lymphocyte ratio (PLR), Glasgow prognostic score (GPS), and prognostic index (PI). We examined 255 patients who received gemcitabine + nab-paclitaxel or FOLFIRINOX as first-line chemotherapy and 159 patients who subsequently underwent second-line chemotherapy. First-line patients with lower CAR had better OS compared to those with a higher CAR (hazard ratio 0.57; 95% confidential index 0.42–77; P < 0.01). Similarly, lower NLR (P = 0.01), higher PNI (P = 0.04), lower PLR (P = 0.03), GPS score of 0 (P < 0.01) and PI score of 0 (P < 0.01) were all associated with better OS. CAR demonstrated the best superiority for determining survival prognosis through the use of area under the curve of time-dependent receiver-operating characteristic curves. Furthermore, a lower CAR before second-line therapy exhibited better OS versus higher CAR (P < 0.01). Therefore, CAR might be a useful biomarker for predicting urPC patient prognosis in both first- and second-line chemotherapy.